THE ROLE OF THE DEPOK GOWESIN COMMUNITY AS AN ACTOR OF CITIZEN PARTICIPATION IN PROMOTING SUSTAINABLE TRANSPORTATION TOWARDS AN ECO CITY IN THE CITY OF DEPOK - Putri Salsadila; Canda Della Agustia Disy; Salwa Adina Zafira; Aniqotul Ummah; Teddy Chrisprimanata Putra (Ikatan Dosen Menulis, 2026)
This study discusses the role of the Gowesin Depok Community as a form of citizen participation in promoting sustainable transportation toward an eco city in Depok City. The study used a qualitative approach with a descriptive method through observation, interviews, documentation, and social media analysis. The results show that the Gowesin Depok Community plays a role in increasing public awareness of environmentally friendly transportation through cycling activities, environmental campaigns, and participation in Indonesia Critical Mass (ICM). The community also contributes to reducing carbon emissions and promoting a sustainable mobility culture in Depok City. However, these efforts still face challenges such as limited bicycle infrastructure, low public awareness among road users, and lack of government support. Therefore, stronger collaboration between the government and the community is needed to achieve sustainable transportation and the eco city concept in Depok City.